A New Distributed Time Synchronization Protocol for Multihop Wireless Networks - Solis, R.; Borkar, V.S.; Kumar, P.R. (Proceedings of the 45th IEEE Conference on Decision and Control, 2006)
A distributed algorithm to achieve accurate time synchronization in large multihop wireless networks is presented. The central idea is to exploit the large number of global constraints that have to be satisfied by a common notion of time in a multihop network. If, at a certain instant, O ij is the clock offset between two neighboring nodes i and j, then for any loop i 1 , i 2 , i 3 , ..., i n , i n + 1 - i 1 in the multihop network, these offsets must satisfy the global constraint Sigma k = 1 n O ik , i k + 1 = 0. Noisy estimates Ocirc ij of O ij are usually arrived at by bilateral exchanges of timestamped messages or local broadcasts. By imposing the large number of global constraints for all the loops in the multihop network, these estimates can be smoothed and made more accurate. A fully distributed and asynchronous algorithm which functions by simple local broadcasts is designed. Changing the time reference node for synchronization is also easy, consisting simply of one node switching on adaptation, and another switching it off. Implementation results on a forty node network, and comparative evaluation against a leading algorithm, are presented